Imaging amyloid: now that we can see it, what does it all mean? - Klunk, William (Henry Stewart Talks, 2010)
Amyloid imaging PET tracers, Development and validation, Amyloid imaging in dementia, Amyloid imaging in mild cognitive impairment, Amyloid imaging in cognitively normal elderly, Consequences of being amyloid-positive
Reviewed at 2020/05/01